Probing the risk markers of mild cognitive impairment and Alzheimer's disease in alloxan-induced diabetic rats: Alzheimer's disease markers in diabetic rats (Indian Journal of Experimental Biology (IJEB), 2024)
Alzheimer's disease (AD) exemplifies a form of diabetes mellitus that selectively affects the brain. In this study we evaluated serum markers and genes linked to AD and investigated the possible link between AD and diabetes. We measured the serum levels of insulin, lactate, citrulline, argininosuccinate, homocitrulline, and AD-associated lipids (2,4-dihydroxybutanoic acid and sphinganine-1-phosphate). We used semi-quantitative reverse transcription polymerase chain reaction to determine the relative gene expression of Rest, Bace1, and Rtn3 in the brain. Western blotting was used to determine the relative protein expression of REST, BACE1, and RTN3 in the brain. Serum from diabetic rats showed significantly higher levels of citrulline, homocitrulline, lactate, 2,4-dihydroxybutanoic acid, and sphinganine-1-phosphate, but lower levels of argininosuccinate and insulin compared with serum from control rats. At the gene level, Bace1 and Rest were significantly increased, whereas Rtn3 was considerably reduced in diabetic compared with control rat brains. At the protein level, BACE1 and RTN3 were significantly increased whereas REST was significantly reduced in diabetic compared with control rat brains. These findings indicate that hyperglycemia and insulin resistance in the brain may be the common element that connects urate turnover and alterations in neural regulatory genes.